Passive radiation refrigeration coating and preparation method thereof
By synergistically constructing materials such as fluoroacrylate emulsions, the spectral modulation and interfacial stability of passive radiation cooling coatings were optimized, solving the problems of single spectrum and weather resistance of existing coatings. This achieved efficient passive cooling and self-cleaning effects, and improved the service life and thermal management performance of the coatings.
Patent Information
- Application Number
- CN202511548061.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2025-12-19
AI Technical Summary
Existing passive radiation cooling coatings suffer from limited spectral control, poor interface stability and weather resistance, resulting in decreased cooling performance and shortened service life, and their surfaces are prone to dust and dirt adsorption.
The synergistic construction of fluoroacrylate emulsion, hollow glass microspheres, sheet-like silica aerogel powder, aluminum fluoride-doped zinc oxide infrared enhancement powder, and superhydrophobic modified fluorosilicone surface additives was achieved through multi-scale spectral modulation and surface self-cleaning system, combined with composite doping and surface fluorination treatment, to optimize the lattice structure and interface stability.
It achieves a synergistic effect of high reflectivity in the solar radiation region and high emissivity in the mid-infrared region. The coating maintains continuous passive cooling throughout the day and night cycle, has self-cleaning ability and excellent resistance to ultraviolet aging, and improves the thermal management efficiency of buildings and equipment.
Smart Images

Figure CN121160160A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of industrial coatings, in particular to a passive radiative cooling coating and a preparation method thereof. BACKGROUND
[0002] At present, in the fields of building energy saving, power equipment cooling and energy storage system heat protection, passive radiative cooling technology has attracted much attention because it can realize temperature difference driven cooling without energy input. The existing passive radiative cooling coating usually introduces high reflective inorganic fillers (such as titanium dioxide, aluminum oxide or hollow glass microspheres) into the resin matrix to improve the reflectivity in the solar spectrum region (0.3-2.5 μm), and uses high emissivity materials (such as zinc oxide, silicon oxide or fluoride) to enhance the infrared emission in the mid-infrared band (8-13 μm).
[0003] However, the traditional system has two deficiencies: Firstly, the spectrum regulation is single and the structure level is insufficient, which leads to limited infrared emission in the atmospheric transparent window region although part of the solar radiation can be reflected, making it difficult to achieve continuous "sub-environmental temperature" cooling effect; Secondly, the interface stability and weather resistance are poor, the bonding force between inorganic fillers and organic resin is weak, and microcracks, delamination or performance degradation may occur under long-term ultraviolet irradiation and hot and humid cycle conditions, which makes the cooling performance significantly decrease with the use time.
[0004] In addition, the surface energy of some systems is high and dust is easily adsorbed, which will reduce the optical reflection performance after long-term exposure, thereby shortening the actual service life. SUMMARY
[0005] In view of the deficiencies of the prior art, the present application provides a passive radiative cooling coating and a preparation method thereof to solve the problems raised in the background art.
[0006] To achieve the above-mentioned purpose, the present application provides the following technical scheme: The present application provides a passive radiative cooling coating, which comprises the following formula: fluorinated acrylate emulsion, 60-120 parts; hollow glass microspheres, 40-90 parts; nanometer titanium dioxide, 20-60 parts; flaky silica aerogel powder, 10-30 parts; polytetrafluoroethylene micro powder, 3-10 parts; hydroxyl-terminated polydimethylsiloxane, 8-20 parts; hydroxy acryl modified silane coupling agent, 1-5 parts; superhydrophobic modified fluorosilicon surface additive, 0.5-3 parts; Nano cerium oxide, 2-8 parts; Aluminum fluoride doped zinc oxide infrared enhancement powder, 5-15 parts; Deionized water, 30-60 parts; Co-dispersant and defoaming agent, 1-3 parts; Leveling agent, 0.5-1.5 parts.
[0007] Further optimize the technical solution, the preparation steps of the aluminum fluoride doped zinc oxide infrared enhancement powder are as follows: Dissolve zinc nitrate hexahydrate and aluminum nitrate in deionized water according to the molar ratio of Zn 2+ : Al 3+ 6-8, adjust the total metal ion concentration of the solution to 0.1-0.2 mol / L, add 0.3-0.6 mol / L of ammonia solution to carry out coprecipitation reaction under the condition of pH 9-10, and obtain the doped precursor powder; Put the obtained doped precursor powder into air atmosphere, heat to 450-500℃ at 5℃ / min, and keep for 2-3h to obtain primary Al-doped ZnO powder, and then carry out low-temperature fluorination modification in ammonium fluoride atmosphere, control the temperature to 300-350℃, and the time to 1.5-2h, so that a stable F - doped layer is formed on the surface; Disperse the fluorinated powder in 2wt.% γ-glycidoxypropylsilane ethanol solution, stir for 0.5-1h, and then dry at 80-90℃ to obtain aluminum fluoride doped zinc oxide infrared enhancement powder.
[0008] Further optimize the technical solution, the coprecipitation reaction obtains the doped precursor powder, and the specific method is: The reaction temperature is controlled at 60±2℃, the stirring speed is 400-500rpm, the hydroxide precursor precipitate is generated after 1-2h of reaction, the precipitate is washed three times by suction filtration, and then placed in a constant temperature drying oven at 100-110℃ for 7-8h to obtain the doped precursor powder.
[0009] Further optimize the technical solution, the flaky silica aerogel powder is induced to grow flaky by freeze orientation drying, which specifically includes the following preparation steps: Mix tetraethoxysilane as precursor according to the molar ratio of tetraethoxysilane: ethanol: water: hydrochloric acid 1:4:10-15:0.05, magnetically stir at 20-25℃ for 0.5-1h to form uniform silica sol, and then stand for aging for 12h to obtain gel body; The gel body with a thickness of 3-5 mm is sliced, and solvent exchange of ethanol and n-hexane is sequentially performed, each step being immersed for 5-6 h, repeated for 2-3 times, and then freeze-dried in a freeze-drying device at a cooling rate of 0.2-0.4 ℃ / min at -50 ℃ for 36-48 h, so that the water sublimation direction induces the arrangement of the lamellar structure, and a sheet-shaped aerogel block is obtained; The obtained block is vacuum dried at 140-150 ℃ for 3-4 h to remove residual solvents, and then placed in anhydrous toluene solution containing 2 wt.% trifluoropropyltrimethoxysilane, refluxed for 1-2 h, and then filtered and dried to obtain sheet-shaped silica aerogel powder.
[0010] Further optimization of the technical solution, the preparation process of the hollow glass microbeads is as follows: The high borosilicon hollow glass microbeads are added into an ethanol solution with a volume fraction of 90%, and amino-propyl triethoxysilane or vinyl triethoxysilane is added as a coupling agent, the concentration of the coupling agent is controlled to be 2 wt.%, the pH is controlled to be 4.5-5.0, the temperature is controlled to be 70-80 ℃, and the stirring reaction is performed for 1-2 h. After the reaction is completed, the product is filtered, washed with ethanol twice, and dried at a constant temperature of 100-110 ℃ for 3-4 h to obtain microbeads with a silanized layer surface with a thickness of 20-40 nm.
[0011] Further optimization of the technical solution, the high borosilicon hollow glass microbeads are pretreated, including: The high borosilicon hollow glass microbeads with an average particle size of 20 μm, a true density of 0.3 g / cm 3 , and a wall thickness of 1.0-1.5 μm are first etched on the surface with a 5 wt.% dilute hydrofluoric acid solution for 25-30 s to remove free oxide layers, and then washed repeatedly with deionized water until neutral, and dried at 100-110 ℃ for 1-2 h.
[0012] Further optimization of the technical solution, the super-hydrophobic modified fluorosilicon surface additive is prepared from a fluorine-containing acrylic monomer, methyl triethoxysilane, and hydroxyl-terminated polydimethylsiloxane, with a molar ratio of 4:1:0.5-1. The preparation method of the super-hydrophobic modified fluorosilicon surface additive is as follows: The fluorine-containing acrylic monomer and the methyl triethoxysilane are dissolved in toluene, and azobisisobutyronitrile is added as an initiator, and a free radical copolymerization reaction is performed at 70-75 ℃ for 4-5 h to obtain a fluorine-containing acrylic-silane copolymer; The hydroxyl-terminated polydimethylsiloxane is condensed with the copolymer under ammonia catalysis, the reaction temperature is 70-80 ℃, and the reaction time is 2-3 h, forming an end-capped fluorosilicon copolymer additive, and the solvent is removed by rotary evaporation, and the product is dried in a vacuum at 50-60 ℃ for 5-6 h to obtain a transparent viscous liquid, i.e., the super-hydrophobic modified fluorosilicon surface additive.
[0013] Further optimization of the technical solution, the fluorine propylene acrylate emulsion with methyl methacrylate, fluorine octyl acrylate, butyl acrylate as main monomer, the molar ratio of methyl methacrylate, fluorine octyl acrylate and butyl acrylate is 6:3:1-2, the preparation method adopts semi-continuous emulsion polymerization method.
[0014] Further optimization of the technical solution, the fluorine propylene acrylate emulsion adopts semi-continuous emulsion polymerization method, including: 1wt.% sodium dodecyl sulfate is added as emulsifier in deionized water, heated to 70-75℃, stirring speed is 200-300rpm, forming monomer mixture; The monomer mixture is added with 0.3wt.% ammonium persulfate solution simultaneously for 1-2h to complete the initiation of polymerization, the reaction is maintained at 70-80℃ for 2-3h and then cooled to 45-50℃; 3-8wt.% of hydroxyl-terminated PDMS is introduced into the system, and 1wt.% of 3-isocyanate propyl triethoxysilane is added as a compatibilizer, and the PDMS is reacted with the emulsion particle surface at 40-50℃ for 1-2h to form a bond; After the reaction is completed, the pH of the system is adjusted to 7.0-7.5, and the stable emulsion, i.e. the acrylate emulsion, is obtained by filtering out the slag.
[0015] A preparation method of passive radiation cooling coating, based on the passive radiation cooling coating described above, comprising the following specific steps: (S1) Pre-dispersion of functional fillers and initial mixing of the system: hollow glass beads, nano-titanium dioxide and flaky silica aerogel powder are added to the fluorine propylene acrylate emulsion, and polytetrafluoroethylene powder is added for high-speed dispersion to form a stable multi-scale scattering base slurry; (S2) Integration of infrared enhancement and weather-resistant fillers: aluminum fluoride doped zinc oxide infrared enhancement powder, nano cerium oxide and hydroxyl acrylate modified silane coupling agent are added to the base slurry to form a composite system with both reflection and radiation functions; (S3) Introduction and dynamic balance control of flexible segments and interface regulators: hydroxyl-terminated polydimethylsiloxane, leveling agent and superhydrophobic modified fluorosilicon surface additives are added to adjust the flexibility and surface energy, and a stable molecular-scale interface structure is formed; (S4) System homogenization, defoaming and construction viscosity control: vacuum defoaming, water viscosity adjustment, and addition of dispersing agents and defoaming agents are carried out to make the system meet the construction requirements in terms of solid content and fluidity, and a uniform milky white coating is obtained; (S5) Film formation, curing and surface structure self-migration: airless spraying is used for film formation, low-temperature drying and room temperature self-crosslinking curing are carried out to form a surface fluorine-silicon self-migration layer, realizing self-cleaning and high reflection characteristics; (S6) Performance detection and finished paint stabilization packaging: performance detection is carried out to the cured coating, and after confirmation of qualification, the finished paint is filtered and packaged for use.
[0016] Compared with the prior art, the present application provides a passive radiation refrigeration coating and a preparation method thereof, which has the following beneficial effects: The passive radiation refrigeration coating and the preparation method thereof realize the synergistic effect of high reflection in the sunlight region and high emission in the mid-infrared region by synergistically constructing a multi-scale spectrum regulation and surface self-cleaning system with fluorine propylene acrylate emulsion, hollow glass microbeads, flaky silica aerogel powder, aluminum fluoride doped zinc oxide infrared enhancement powder and super-hydrophobic modified fluorosilicon surface additives. The coating can maintain continuous passive refrigeration in the day-night cycle, and the coating surface has self-cleaning ability and excellent ultraviolet aging resistance, and can maintain high reflectivity and high radiation emissivity for a long time in complex outdoor environments, thereby significantly improving the thermal management efficiency of buildings and equipment, and having good engineering application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings needed in the embodiment description will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor.
[0018] Figure 1 A flowchart of a passive radiation refrigeration coating preparation method proposed by the present application. DETAILED DESCRIPTION
[0019] In order to make the above-mentioned purposes, features and advantages of the present application more apparent and easy to understand, the specific embodiments of the present application will be described in detail below with reference to the drawings of the specification.
[0020] In the following description, many specific details are set forth in order to provide a thorough understanding of the present application, but the present application can also be implemented in other ways different from the description, and those skilled in the art can make similar generalizations without departing from the connotation of the present application, therefore the present application is not limited by the specific embodiments disclosed below.
[0021] Secondly, the "one embodiment" or "embodiment" referred to herein means that the specific features, structures or characteristics can be included in at least one implementation of the present application. "In one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an embodiment that is independent of or mutually exclusive with other embodiments.
[0022] A passive radiation refrigeration coating, comprising the following mass parts of formula: Fluoroacrylate emulsion, 60-120 parts; as the main film-forming matrix, it has excellent UV resistance, weather resistance and low thermal conductivity, and is the structural backbone of the entire coating.
[0023] Hollow glass microbeads, 40-90 parts; by multiple Mie scattering, the reflectivity of 0.3-2.5 µm sunlight is greatly improved, and the bulk density of the material is reduced to reduce heat conduction.
[0024] Nano-titanium dioxide, 20-60 parts; as a strong scattering particle, it forms a multi-angle reflection path in the visible and near-infrared bands, significantly improving the overall solar reflectivity.
[0025] Silica aerogel powder in sheet form, 10-30 parts; with low refractive index and high porosity, it can provide a high-emissivity channel in the mid-infrared 8-13 µm range while suppressing heat conduction transmission.
[0026] Polytetrafluoroethylene micro powder, 3-10 parts; it gives the surface self-cleaning property and low surface energy, preventing spectral performance degradation caused by dust adhesion and improving durability.
[0027] Hydroxyl-terminated polydimethylsiloxane PDMS, 8-20 parts; it forms a flexible network in the coating, improving heat cycle stability and improving micro thermal expansion compatibility.
[0028] Hydroxyl acryl-modified silane coupling agent, 1-5 parts; it is used to improve the interfacial bonding between inorganic fillers and organic matrix, ensuring long-term spectral stability and mechanical strength.
[0029] Super-hydrophobic modified fluorosilicon surface additive, 0.5-3 parts; it migrates to the surface during curing, forming a super-low surface energy layer, improving dust and oil resistance.
[0030] Nano cerium oxide, 2-8 parts; it has high UV absorption capacity and can prevent matrix aging caused by titanium dioxide photocatalysis, while enhancing anti-aging performance.
[0031] Aluminum fluoride-doped zinc oxide infrared enhancement powder, 5-15 parts; it has high emissivity in the mid-infrared region, acting as an infrared radiation enhancer, making the coating have a cooling effect at night and during the day.
[0032] Deionized water, 30-60 parts; as a dispersion medium, it ensures stable dispersion of the emulsion and nanofillers and facilitates construction and formulation.
[0033] Dispersion aid and defoaming agent, 1-3 parts; used to stabilize the system, eliminate bubbles and improve construction fluidity.
[0034] Leveling agent, 0.5-1.5 parts; used to improve film flatness and spectral consistency, ensuring that the coating surface has no interference spots and local spectral distortion.
[0035] The preparation steps of the aluminum fluoride-doped zinc oxide infrared enhancement powder are as follows: Zinc nitrate hexahydrate and aluminum nitrate are dissolved in deionized water according to the molar ratio of Zn 2+ : Al 3+ 6-8, the total metal ion concentration of the solution is adjusted to 0.1-0.2 mol / L, 0.3-0.6 mol / L of ammonia solution is added to the solution under the condition of pH 9-10, the reaction temperature is controlled at 60±2℃, the stirring speed is 400-500 rpm, and the hydroxide precursor precipitate is generated after 1-2 h of reaction. The precipitate is washed three times by suction filtration and then dried in a constant temperature drying box at 100-110℃ for 7-8 h to obtain the doped precursor powder; The obtained doped precursor powder is placed in an air atmosphere and heated to 450-500℃ at a rate of 5℃ / min and kept for 2-3 h to obtain the primary Al-doped ZnO powder. Then, low-temperature fluorination modification is carried out in an ammonium fluoride atmosphere, the temperature is controlled at 300-350℃, and the time is 1.5-2 h, so that a stable F - doped layer is formed on the surface, which prevents agglomeration and improves dielectric properties; To improve dispersibility, the fluorinated powder is dispersed in a 2wt.% γ-glycidoxypropyltrimethoxysilane (KH560) ethanol solution, stirred for 0.5-1 h and dried at 80-90℃ to obtain the aluminum fluoride-doped zinc oxide infrared enhancement powder.
[0036] The average particle size D50 of the final powder is 80-150 nm, and the specific surface area is 45-60 m 2 / g. The average emissivity of the powder in the 8-13μm range is above 0.92, and the absorption rate in the 0.3-2.5μm solar light range is less than 0.07, which is suitable for the middle infrared enhancement layer of passive radiative cooling coating. The method realizes the coupling optimization of lattice structure stability and spectral emissivity through composite doping and surface fluorination treatment.
[0037] The flaky silica aerogel powder is prepared by freeze orientation drying and inducing flake growth, and the preparation steps are as follows: TEOS is used as the precursor, and the molar ratio of TEOS: ethanol: water: hydrochloric acid is 1:4:10-15:0.05, the uniform silica sol is formed by magnetic stirring at 20-25℃ for 0.5-1 h, and then the gel body is obtained by standing for 12 h; The gel body with a thickness of 3-5 mm is sliced, and solvent exchange of ethanol and n-hexane is sequentially performed, each step being immersed for 5-6 h, repeated 2-3 times to reduce capillary force; then, the gel body is freeze-dried in a freeze-drying device at a cooling rate of 0.2-0.4 ℃ / min at -50 ℃ for 36-48 h to induce the arrangement of the lamellar structure in the sublimation direction of water, and a sheet-shaped aerogel block is obtained; The obtained block is vacuum dried at 140-150 ℃ for 3-4 h to remove residual solvent, and to improve hydrophobicity, the obtained aerogel is crushed into micro-sheet-shaped particles with a size of 1-5 μm, and then placed in anhydrous toluene solution containing 2 wt.% trifluoropropyltrimethoxysilane, and refluxed for 1-2 h, and then filtered and dried to obtain sheet-shaped silica aerogel powder.
[0038] The average thickness of the final powder is 50-200 nm, the specific surface area is 800-1100 m 2 / g, and the pore size distribution is concentrated in the range of 20-60 nm. The micro-sheet-shaped arrangement of the structure forms multi-directional diffuse reflection and absorption channels in the mid-infrared band, which can effectively improve the radiation emissivity of the coating while maintaining extremely low thermal conductivity (0.018 W / m·K).
[0039] The preparation process of the hollow glass microbeads is as follows: The high-boron-silicon hollow glass microbeads with an average particle size of 20 μm, a true density of 0.3 g / cm 3 , and a wall thickness of 1.0-1.5 μm are selected, and then the surface is etched with 5 wt.% dilute hydrofluoric acid solution for 25-30 s to remove the free oxide layer, and then washed repeatedly with deionized water until neutral, and dried at 100-110 ℃ for 1-2 h; The dried microbeads are added to an ethanol solution with a volume fraction of 90%, and amino-propyl triethoxysilane (KH550) or vinyl triethoxysilane (VTES) is added as a coupling agent, the concentration of the coupling agent is controlled to be 2 wt.%, the pH is controlled to be 4.5-5.0, the temperature is controlled to be 70-80 ℃, and the stirring reaction is performed for 1-2 h; After the reaction is completed, the microbeads are filtered, washed twice with ethanol, and dried at 100-110 ℃ for 3-4 h to obtain microbeads with a silanized layer surface with a thickness of 20-40 nm.
[0040] To further improve the dispersion stability, 1 wt.% of hydroxyl-terminated PDMS can be introduced in the post-processing to perform light coating, so that the surface contact angle is increased from 45° to 110°, and the surface energy is reduced to below 25 mN / m. According to the ultraviolet-visible-near-infrared spectrum test, the average reflectivity of the microbeads in the 0.3-2.5 μm segment can reach 0.95 or more, and when blended with fluoropropylene emulsion, the system viscosity is stable at 1500-1800 mPa·s, and there is no obvious sedimentation after 24 h of dispersion. This method ensures the compatibility of high scattering and high stability through chemical bonding and flexible interface construction.
[0041] wherein the superhydrophobic modified fluorosilicon surface additive is prepared from fluorine-containing acrylic monomer (2,2,3,4,4,4-hexafluorobutyl acrylate, HFBA), methyl triethoxysilane (MTES) and hydroxyl-terminated polydimethylsiloxane (PDMS-OH, molecular weight 2000-3000) as raw materials, and the molar ratio is 4:1:0.5-1.
[0042] The preparation method of the superhydrophobic modified fluorosilicon surface additive is as follows: The fluorine-containing acrylic monomer and the methyl triethoxysilane are dissolved in toluene (solid content 20 wt.%), and azobisisobutyronitrile (AIBN) is added as an initiator (mass fraction 0.5 %), and a free radical copolymerization reaction is carried out at 70-75 °C for 4-5 h to obtain a fluorine-containing acrylic-silane copolymer; The hydroxyl-terminated polydimethylsiloxane is condensed with the copolymer under ammonia catalysis, the reaction temperature is 70-80 °C, and the reaction time is 2-3 h to form an end-capped fluorosilicon copolymer additive, and the solvent is removed by rotary evaporation, and the vacuum drying is carried out at 50-60 °C for 5-6 h to obtain a transparent viscous liquid, i.e. the superhydrophobic modified fluorosilicon surface additive.
[0043] The viscosity of the obtained additive is 400-800 mPa·s, the mass fraction of fluorine element is 15-25 %, and the Si content is 5-8 %. The contact angle test shows that the surface contact angle of the additive after film formation can reach 125-135 °. When used, the additive is added at 0.5-1.5 wt.% of the total mass of the emulsion, and is dispersed at a stirring and shearing rate of 400-500 rpm for 10 min, and can automatically migrate to the surface layer of the coating during the post-curing process to form a low surface energy film with a thickness of about 100-200 nm. The preparation route combines the surface self-organization effect of fluorocarbon and siloxane segments at the molecular level.
[0044] The fluorine-containing acrylate emulsion takes methyl methacrylate (MMA), fluoro-octyl acrylate (FDA) and butyl acrylate (BA) as main monomers, and the molar ratio of methyl methacrylate, fluoro-octyl acrylate and butyl acrylate is 6:3:1-2, and the preparation method adopts a semi-continuous emulsion polymerization method.
[0045] Further, the semi-continuous emulsion polymerization method used by the fluorine-containing acrylate emulsion comprises: 1 wt.% sodium dodecyl sulfate is added as an emulsifier in deionized water, the temperature is raised to 70-75 °C, and the stirring speed is 200-300 rpm to form a monomer mixture; The monomer mixture and 0.3 wt.% ammonium persulfate solution are simultaneously added dropwise for 1-2 h to complete the initiation polymerization, and after the reaction is maintained at 70-80 °C for 2-3 h, it is cooled to 45-50 °C; The 3-8 wt.% of hydroxyl-terminated PDMS (molecular weight 1000-2000) is introduced into the system, and 1 wt.% of 3-isocyanate propyl triethoxy silane is added as a compatibilizer, and the PDMS is reacted with the surface of the emulsion particles to form a bond at 40-50℃ for 1-2h; After the reaction is completed, the pH of the system is adjusted to 7.0-7.5, and the stable emulsion, i.e. the fluorine propylene acrylate emulsion, is obtained by filtering out the slag.
[0046] The obtained emulsion has a solid content of 45-50%, a particle size distribution D50 of 180-220 nm, and a Zeta potential of about -45 mV. After film formation, the infrared transmittance of the coating layer in the 8-13 μm interval can reach more than 0.85, the glass transition temperature is about 40℃, and the flexibility is excellent. The emulsion forms a nano-scale energy barrier through the micro-interpenetration of fluorocarbon hard chains and siloxane soft chains, which not only maintains the integrity of the high-reflectivity coating layer, but also improves the transmittance balance of the infrared emission layer, providing a stable film-forming basis for the passive radiation cooling system.
[0047] The nano-titanium dioxide is selected as anatase TiO2 (P25 type, average particle size about 25 nm), which has high scattering efficiency and low light absorption characteristics, and is used to enhance the reflectivity in the sunlight band.
[0048] The nano-cerium oxide is selected as CeO2 (Guoceramics type CeO2-20N) with a particle size of about 20 nm, which has strong ultraviolet absorption capacity and is used to prevent titanium dioxide photocatalytic aging and improve weather resistance.
[0049] The hydroxyl-terminated polydimethylsiloxane adopts PDMS-OH (Dow Corning 200 Fluid OH type) with a viscosity of 100 mPa·s, which is used as a flexible chain segment to adjust the thermal expansion of the coating film and improve the heat cycle stability.
[0050] The hydroxyl acrylate modified silane coupling agent adopts γ-methacryloyloxypropyl trimethoxysilane (KH570), which is used to enhance the interfacial bonding force between the inorganic filler and the emulsion matrix.
[0051] The dispersant aid is selected as a high molecular dispersant of BYK-110 type, and the defoamer is selected as TEGO Foamex 805, both of which are used to ensure the dispersion stability of the nano-filler and the construction property of the system.
[0052] The leveling agent adopts a fluorine-modified polyacrylate leveling agent BYK-333, which can improve the surface tension of the coating layer and ensure the spectral consistency.
[0053] The deionized water is an experimental grade solvent with a purity of > 18 MΩ·cm, which is used as a dispersion medium of the system and regulates the viscosity of the coating.
[0054] Reference Figure 1A preparation method of a passive radiative cooling coating, which is prepared based on the passive radiative cooling coating described above, comprises the following specific steps: (S1) Pre-dispersion of functional fillers and initial mixing of the system; First, pour the fluoropropenoate emulsion as the film-forming matrix into a high-speed dispersion kettle, control the initial rotation speed to be 300 rpm, and make the emulsion form a uniform flow system at room temperature (20-25°C). Then, add the hollow glass microbeads, nano-titanium dioxide, and flaky silica aerogel powder in sequence. To avoid agglomeration of the nanoparticles, stir while adding, and gradually increase the stirring speed to 800 rpm, and continue to disperse for 40-60 min. To improve the wettability of the particle surface, add a dispersing aid to the system, so that it is fully adsorbed on the surface of the inorganic particles to form a stable electrostatic and steric barrier. During the dispersion process, further add polytetrafluoroethylene powder as a surface control and wear-resistant aid. The polytetrafluoroethylene powder can uniformly coat the surface of the hollow glass microbeads and nano-titanium dioxide after dispersion, forming an interface layer with low refractive index and low surface energy, thereby improving the overall anti-pollution and wear resistance without affecting the visible light reflection performance. After pre-dispersion, the system should be in a milky white uniform slurry state, and there should be no obvious sedimentation after standing for 10 min. The slurry output in this step is the basis for subsequent compounding, and determines the consistency and scattering uniformity of the overall coating spectrum structure.
[0055] (S2) Compounding and integration of infrared enhancement and weather-resistant fillers; In the dispersion system output in step S1, slowly add aluminum fluoride doped zinc oxide infrared enhancement powder and nano cerium oxide. During the addition process, maintain the stirring speed of the system at 600 rpm, and stir at 40°C for 1 h to promote interface bonding. To further improve the interface bonding strength and weather resistance of the fillers, add a hydroxy acrylate modified silane coupling agent, which hydrolyzes and forms a siloxane bond network in the reaction system, thereby forming a chemical bridging structure between the organic matrix and the inorganic fillers. After completing this step, the slurry realizes the preliminary construction of the "scattering layer-radiation layer-protection layer" in the microstructure, laying a foundation for subsequent performance stabilization. Through the superposition effect of composite scattering and selective emission, the system has dual passive cooling capability in both daytime and nighttime.
[0056] (S3) Introduction of flexible segments and interface regulators and dynamic balance control; The hydroxyl-terminated polydimethylsiloxane is slowly added to the slurry obtained in step S2, and stirring is continued for 40 min, followed by the addition of a leveling agent, so that the surface tension of the system is controlled in the range of 28-32 mN / m, to improve the flow spreading property. At this time, the stirring temperature is maintained at 30°C, and the shear rate is 500 rpm. After stirring for 30 min, the system becomes a translucent emulsion. To stabilize the combined system of the inorganic phase and the organic phase, a super-hydrophobic modified fluorosilicon surface additive is continuously added, and mixing is carried out under low shear for 20 min. The surface energy of the system is reduced at the molecular level, so that the coating forms a naturally migrating low-energy layer after curing. This step is controlled by dynamic balance, so that the coating system has completed the molecular-scale softening and surface energy regulation before film formation, providing conditions for the self-cleaning property and thermal stability after curing.
[0057] (S4) System homogenization, defoaming and viscosity control; The composite system obtained in step S3 is transferred into a vacuum defoaming stirring tank, and a vacuum condition of -0.08 MPa is applied for 20 min to remove micro-bubbles and prevent optical distortion after film formation. Then, the amount of deionized water is gradually adjusted so that the solid content of the system is stabilized in the range of 50±2 wt.%, and the final viscosity is maintained at 1500-1800 mPa·s. At this time, the light reflectivity of the system is detected, and if the average reflectivity in the range of 400-2500 nm is less than 0.93, TiO2 is appropriately supplemented to ensure stable optical performance. A defoaming agent is further added and stirred at low speed for 5 min to eliminate surface residual bubbles. After the system is regulated, large particles or undispersed substances are removed by filtration (screen hole 100 μm), and a uniform milky white liquid coating is obtained. The key of this step is to achieve optical layer thickness consistency by vacuum defoaming and viscosity precise control, to prevent the occurrence of optical interference lines or uneven scattering during construction. Through multiple sampling detection, the system density should be 1.05±0.02 g / cm 3 , and the pH is maintained at about 7.0. This process ensures that the coating has good flow spreading property under the conditions of spraying, rolling or brushing, while ensuring stable particle distribution, which is the key link to ensure consistent final performance.
[0058] (S5) Film formation and curing, and surface structure self-migration; The homogeneous coating obtained in step S4 is applied to the surface of an oil and dust removed substrate (such as an aluminum alloy plate, a galvanized steel plate or a concrete substrate), using airless spraying, with a nozzle aperture of 1.0-1.5 mm and a spraying pressure of 0.3-0.4 MPa. The thickness of each layer is controlled at 60-80 μm, and the second layer is sprayed after 30 min, with a total film thickness of about 120-150 μm. After the coating is left to stand for 1 h, it is dried in a constant temperature oven at 60 °C for 3 h to remove residual moisture, and then self-crosslinking curing is carried out at room temperature for 48 h. During the curing process, the super-hydrophobic modified fluorosilicon surface additive molecules automatically migrate to the surface layer of the coating to form a low surface energy film layer (about 100-200 nm thick), with a surface contact angle of up to 130° or more, thereby significantly improving the dust and stain resistance and infrared radiation stability. At the same time, the thermal motion of the PDMS flexible chain segment during the curing stage forms a flexible connection structure between the microparticles, improving the mechanical adhesion and thermal shock resistance. After curing, the coating surface is smooth, bubble-free and pinhole-free, with a reflectivity maintained at 0.94 or more. This step realizes the construction of a self-organized film layer through a thermal-interface synergistic mechanism, so that the surface spectral properties remain stable during the use period, with both self-cleaning and radiation efficiency.
[0059] (S6) Performance detection and finished coating stabilization packaging The sample after film formation and curing needs to be placed in a standard environment (temperature 23±2 °C, relative humidity 50±5%) for 72 h for performance stabilization. Then the spectral and thermal performance of the finished coating is detected. The qualified product is packed in a sealed barrel after being filtered through an 80 mesh sieve to avoid exposure to sunlight and low temperature freezing. This step ensures that the final coating performance parameters can be repeatedly verified, and the engineering reliability of the system is clear through standardized testing. The passive radiation refrigeration coating prepared by the above six-step process has the comprehensive performance of high reflectivity, high emission, anti-pollution and weather resistance, and can maintain stable passive refrigeration effect in outdoor high temperature environment for a long time.
[0060] Example 1 Fluorine propylene acrylate emulsion 60 parts; hollow glass microbeads 40 parts; nano titanium dioxide 20 parts; flaky silica aerogel powder 10 parts; polytetrafluoroethylene micro powder 3 parts; hydroxyl-terminated polydimethylsiloxane 8 parts; hydroxyl acrylate modified silane coupling agent 1 part; super-hydrophobic modified fluorosilicon surface additive 0.5 parts; nano cerium oxide 2 parts; fluorinated aluminum doped zinc oxide infrared enhancement powder 5 parts; deionized water 30 parts; dispersant and defoaming agent 1 part; leveling agent 0.5 parts.
[0061] The preparation steps of the fluorinated aluminum doped zinc oxide infrared enhancement powder are as follows: Zinc nitrate hexahydrate and aluminum nitrate are mixed according to Zn 2+ and Al 3+The molar ratio of 100:8 was dissolved in deionized water, the total metal ion concentration of the solution was adjusted to 0.2 mol / L, 0.6 mol / L ammonia solution was added to the condition of pH 10, the reaction temperature was controlled at 60±2℃, the stirring speed was 500 rpm, the hydroxide precursor precipitate was generated after 2h reaction, the precipitate was filtered and washed three times, and then placed in a constant temperature drying oven at 110℃ for 8h to obtain the doped precursor powder; The obtained doped precursor powder was placed in an air atmosphere, heated to 500℃ at a rate of 5℃ / min and kept for 3h to obtain primary Al-doped ZnO powder, and then low-temperature fluorination modification was carried out in an ammonium fluoride atmosphere, with the temperature controlled at 350℃ and the time controlled at 2h. The fluorinated powder was dispersed in a 2wt.% γ-glycidoxypropyltrimethoxysilane (KH560) ethanol solution, stirred for 1h and dried at 90℃ to obtain aluminum fluoride-doped zinc oxide infrared enhancement powder.
[0062] The flaky silica aerogel powder was prepared by freeze orientation drying and inducing lamellar growth, and the preparation process included the following steps: Ethanol: water: hydrochloric acid was 1:4:15:0.05, and then the uniform silica sol was formed by magnetic stirring at 25℃ for 1h, and then the gel body was obtained by standing and aging for 12h; The gel body with a thickness of 3–5mm was sliced, and solvent exchange of ethanol and n-hexane was carried out in sequence, with each step of immersion for 6h, and repeated for 3 times; then the flaky aerogel block was obtained by freeze drying in a freeze drying device at a cooling rate of 0.4℃ / min at –50℃ for 48h, so that the water sublimation direction induced lamellar structure arrangement, and the flaky aerogel block was obtained. The obtained block was vacuum dried at 150℃ for 4h to remove residual solvents, and then the flaky aerogel powder was obtained by crushing the obtained aerogel into 1–5μm microflaky particles, and then placing it in anhydrous toluene solution containing 2wt.% trifluoropropyltrimethoxysilane, refluxing for 2h, and then drying by filtration to obtain the flaky silica aerogel powder.
[0063] The preparation process of the hollow glass microbeads is as follows: The high borosilicate hollow glass microbeads with an average particle size of 20μm, a true density of 0.3g / cm 3 , and a wall thickness of 1.0–1.5μm were first etched on the surface with 5wt.% dilute hydrofluoric acid solution for 30s to remove the free oxide layer, and then washed repeatedly with deionized water until neutral, and dried at 110℃ for 2h. The dried microbeads were added to a 90% volume fraction of ethanol solution, and aminopropyl triethoxysilane (KH550) or vinyl triethoxysilane (VTES) was added as a coupling agent, the concentration of the coupling agent was controlled to be 2 wt.%, the pH was 5.0, the temperature was 80°C, and the stirring reaction was performed for 2 h; After the reaction was completed, the product was filtered and washed twice with ethanol, and then dried at 110°C for 4 h to obtain the microbeads with a silanized layer surface with a thickness of 20-40 nm.
[0064] The super-hydrophobic modified fluorosilicon surface additive was prepared using fluorine-containing acrylic monomer (2,2,3,4,4,4-hexafluorobutyl acrylate, HFBA), methyl triethoxysilane (MTES), and hydroxyl-terminated polydimethylsiloxane (PDMS-OH, molecular weight 2000-3000) as raw materials, and the molar ratio was 4:1:1.
[0065] The preparation method of the super-hydrophobic modified fluorosilicon surface additive was as follows: The fluorine-containing acrylic monomer and the methyl triethoxysilane were dissolved in toluene (solid content 20 wt.%), and azobisisobutyronitrile (AIBN) was added as an initiator (mass fraction 0.5 %), and a free radical copolymerization reaction was performed at 75°C for 5 h to obtain a fluorine-containing acrylic-silane copolymer; The hydroxyl-terminated polydimethylsiloxane was condensed with the copolymer under the catalysis of ammonia, the reaction temperature was 80°C, and the reaction time was 3 h to form a terminal-sealed fluorosilicon copolymer additive, and the solvent was removed by rotary evaporation, and the product was dried in a vacuum at 60°C for 6 h to obtain a transparent viscous liquid, i.e., the super-hydrophobic modified fluorosilicon surface additive.
[0066] The fluorine-containing acrylate emulsion was prepared using methyl methacrylate (MMA), fluoro-octyl acrylate (FDA), and butyl acrylate (BA) as main monomers, and the molar ratio of methyl methacrylate, fluoro-octyl acrylate, and butyl acrylate was 6:3:2, and a semi-continuous emulsion polymerization method was used.
[0067] Further, the semi-continuous emulsion polymerization method used for the fluorine-containing acrylate emulsion included the following steps: Deionized water was added with 1 wt.% sodium dodecyl sulfate as an emulsifier, the temperature was raised to 75°C, and the stirring speed was 300 rpm to form a monomer mixture; The monomer mixture was added with 0.3 wt.% ammonium persulfate solution simultaneously dropwise for 2 h to complete the initiation of polymerization, the reaction was maintained at 80°C for 3 h, and then cooled to 50°C; 8 wt.% of hydroxyl-terminated PDMS (molecular weight 1000-2000) was introduced into the system, and 1 wt.% of 3-isocyanate propyl triethoxysilane was added as a compatibilizer, and the system was stirred at 50°C for 2 h to bond the PDMS to the surface of the emulsion particles; After the reaction, the pH of the system is adjusted to 7.5, and the residue is removed by filtration to obtain a stable emulsion, i.e. a fluoropropenoate emulsion.
[0068] The nano-titanium dioxide is selected from anatase TiO2 (P25 type, average particle size about 25 nm).
[0069] The nano-cerium oxide is selected from CeO2 (Guoceramics type CeO2-20N) with a particle size of about 20 nm.
[0070] The hydroxyl-terminated polydimethylsiloxane is PDMS-OH (Dow Corning 200 Fluid OH type) with a viscosity of 100 mPa·s.
[0071] The hydroxyl-acrylic acid modified silane coupling agent is γ-methacryloyloxypropyl trimethoxysilane (KH570).
[0072] The co-dispersant is selected from a high molecular dispersant of BYK-110 type, and the defoaming agent is selected from TEGO Foamex 805.
[0073] The leveling agent is a fluorine-modified polyacrylate leveling agent BYK-333.
[0074] The deionized water is an experimental grade solvent with a purity of > 18 MΩ·cm.
[0075] The preparation method of the passive radiation cooling coating comprises the following specific steps: (S1) pre-dispersion of functional fillers and initial mixing of the system; First, the fluoropropenoate emulsion is poured into a high-speed dispersion kettle as a film-forming matrix, and the initial rotating speed is controlled at 300 rpm to form a uniform flow system at room temperature (20-25℃). Then, hollow glass microspheres, nano-titanium dioxide and flaky silica aerogel powder are added in sequence. While adding, stirring is performed, and the stirring speed is gradually increased to 800 rpm, and the dispersion is continued for 60 min. The co-dispersant is added to the system to be fully adsorbed on the surface of the inorganic particles. During the dispersion process, polytetrafluoroethylene powder is added as a surface control and wear-resistant aid. After pre-dispersion, the system should be in a milky white uniform slurry state, and no obvious sedimentation is observed after standing for 10 min.
[0076] (S2) compounding and integrating of infrared enhancement and weather-resistant fillers; In the dispersion system output in step S1, aluminum fluoride doped zinc oxide infrared enhancement powder and nano-cerium oxide are slowly added. During the addition process, the stirring speed of the system is maintained at 600 rpm, and stirring is performed at 40℃ for 1 h to promote interface bonding. The hydroxyl-acrylic acid modified silane coupling agent is added to hydrolyze in the reaction system and form a siloxane network.
[0077] (S3) Introduction of flexible segment and interface regulator and dynamic balance control; Hydroxyl-terminated polydimethylsiloxane was slowly added to the slurry obtained in step S2, and stirring was continued for 40 min, followed by the addition of a leveling agent, so that the surface tension of the system was controlled in the range of 28-32 mN / m to improve the flow spreading property. At this time, the stirring temperature was maintained at 30°C, and the shear rate was 500 rpm. After stirring for 30 min, the system became a translucent emulsion. Superhydrophobic modified fluorosilicon surface additive was continuously added, and mixing was carried out under low shear for 20 min. The surface energy of the system was reduced at the molecular level, so that the coating formed a naturally migrating low-energy layer after curing.
[0078] (S4) System homogenization, defoaming and construction viscosity control; The composite system obtained in step S3 was transferred into a vacuum defoaming stirring tank, and vacuum defoaming was carried out at-0.08 MPa for 20 min to remove microbubbles. Subsequently, the amount of deionized water was adjusted step by step so that the solid content of the system was stabilized in the range of 50±2 wt.%, and the final viscosity was maintained at 1500-1800 mPa·s. Defoaming agent was further added and stirred at low speed for 5 min to eliminate surface residual bubbles. After the system was regulated, large particles or undispersed substances were removed by filtration (screen aperture 100 μm), and a uniform milky white liquid coating was obtained.
[0079] (S5) Film formation and curing and surface structure self-migration; The homogeneous coating obtained in step S4 was applied to the surface of a substrate treated by oil and dust removal. Airless spraying was used, the nozzle diameter was 1.0-1.5 mm, and the spraying pressure was 0.3-0.4 MPa. The thickness of each layer was controlled in the range of 60-80 μm, and the second layer was sprayed after 30 min, and the total film thickness was about 120-150 μm. After the coating was placed in a constant temperature oven at 60°C for 3 h to remove residual moisture, it was then self-crosslinked and cured at room temperature for 48 h.
[0080] (S6) Performance detection and finished product coating stabilization and packaging; The sample after film formation and curing needs to be placed in a standard environment for 72 h for performance stabilization. Subsequently, the spectral and thermal performance of the finished coating was detected. The qualified product was packed in a sealed barrel after being filtered through 80 meshes to avoid exposure to sunlight and low-temperature freezing.
[0081] Example 2: Fluoropropyl acrylate emulsion 90 parts; hollow glass microbeads 65 parts; nano-titanium dioxide 40 parts; flaky silica aerogel powder 20 parts; polytetrafluoroethylene micro powder 6 parts; hydroxyl-terminated polydimethylsiloxane 14 parts; hydroxyl acrylate modified silane coupling agent 2.5 parts; superhydrophobic modified fluorosilicon surface additive 1.5 parts; nano cerium oxide 4 parts; aluminum fluoride doped zinc oxide infrared enhancement powder 10 parts; deionized water 45 parts; dispersing aid and defoaming agent 2 parts; leveling agent 1 part.
[0082] The preparation method of each formula and its coating is the same as that of Example 1.
[0083] Example 3: Fluorinated acrylate emulsion 120 parts; hollow glass microbeads 90 parts; nano-titanium dioxide 60 parts; flaky silica aerogel powder 30 parts; polytetrafluoroethylene micro powder 10 parts; hydroxyl-terminated polydimethylsiloxane 20 parts; hydroxyl acrylate modified silane coupling agent 5 parts; super-hydrophobic modified fluorosilicon surface additive 3 parts; nano-cerium oxide 8 parts; aluminum fluoride doped zinc oxide infrared enhancement powder 15 parts; deionized water 60 parts; dispersant and defoaming agent 3 parts; leveling agent 1.5 parts.
[0084] The preparation method of each formula and its coating is the same as that of Example 1.
[0085] Comparative Example 1: Remove the aluminum fluoride doped zinc oxide infrared enhancement powder, the rest is the same as Example 2. The preparation method of each formula and its coating is the same as that of Example 1 (excluding the preparation method of aluminum fluoride doped zinc oxide infrared enhancement powder).
[0086] Comparative Example 2: Remove the flaky silica aerogel powder, the rest is the same as Example 2 (excluding the preparation method of flaky silica aerogel powder).
[0087] The above examples and comparative examples are tested for performance, and the test contents are as follows: Average solar reflectance (0.3-2.5 μm) test content: The spectral reflectance of the sample in the 0.3-2.5 μm band is measured by ultraviolet-visible-near infrared spectrophotometer. When testing, the coating sample is sprayed on an aluminum plate substrate with a film thickness of about 120 μm, and placed in a standard light condition (AM1.5, 1000 W / m 2 ) for integral reflectance measurement. The average reflectance is calculated by the integrating sphere method, and the higher the reflectance, the less the absorption of solar radiation, and the stronger the passive cooling ability of the coating in the direct sunlight environment.
[0088] Infrared emissivity (8-13 μm) test content: The radiation emissivity of the sample is tested in the 8-13 μm band by Fourier transform infrared spectrometer. The sample is placed on a standard black body contrast platform, and the emissivity is calculated by comparing the difference in radiation intensity between the coating sample and the black body standard. The test temperature is controlled at 25±1℃, and the relative humidity is 50±5%. High emissivity indicates that the coating can more effectively radiate heat to outer space through the atmospheric "transparent window", which is a key indicator for realizing continuous cooling day and night.
[0089] Surface cooling amplitude (℃) test content: The aluminum plate sprayed with the sample coating and the uncoated control plate were placed side by side under natural sunlight conditions, with a thermocouple attached to the back for real-time temperature monitoring. The test time was from 10:00 to 15:00, and the highest temperature difference in the stable stage was recorded. The results were expressed as the temperature drop amplitude (ΔT) of the sample surface relative to the control sample. The test simulated the typical building roof exposure environment to evaluate the actual passive cooling effect of the coating.
[0090] Ultraviolet aging 1000h change rate (%) test content: An ultraviolet accelerated aging test chamber (UVA-340 lamp tube, irradiation intensity 0.68 W / m 2 ) was used for ultraviolet aging test, aging time 1000h, cycle condition 8h light (60℃) + 4h condensation (50℃). The solar reflectance and infrared emissivity of the coating were measured before and after the test, and the aging stability was characterized by the performance change rate. The smaller the change rate, the more stable the spectral performance and structural integrity of the coating under long-term outdoor ultraviolet irradiation.
[0091] Stain resistance performance (contact angle °) test content: A contact angle measuring instrument was used to test the static water contact angle on the surface of the coating. Deionized water was used as the test droplet, with a droplet volume of 5 μL. The droplet profile was photographed at room temperature, and the contact angle was calculated by image analysis software. A contact angle greater than 120° indicates that the coating surface has superhydrophobic properties, effectively resisting dust and water vapor adhesion, thereby maintaining high reflectivity and high radiation efficiency in long-term exposure environments.
[0092] The test results are shown in Table 1.
[0093] Table 1
[0094] The test results show that Examples 1-3 all exhibit high solar reflectivity and infrared emissivity, among which Example 2 achieves the best balance between spectral performance and weather resistance, with a surface temperature drop of 8.3°C and a performance decay of only 2.1% after ultraviolet aging. In contrast, Comparative Example 1, which removes the aluminum fluoride-doped zinc oxide infrared enhancement powder, has a significantly reduced infrared emissivity, resulting in a decrease in overall cooling performance; Comparative Example 2, which lacks the flaky silica aerogel powder, has an uneven reflective layer structure, and both the cooling amplitude and weather resistance are significantly weakened.
[0095] Therefore, aluminum fluoride-doped zinc oxide and flaky silica aerogel play a key role in forming a high-emissivity and high-stability structure, and the synergistic design of the passive radiation cooling coating formula significantly improves the overall performance of the passive radiation cooling coating.
[0096] It should be noted that the above examples are only used to illustrate the technical solutions of the present application but not limit the present application. Although the present application is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or equivalently replaced, without departing from the spirit and scope of the technical solutions of the present application, which should be covered in the scope of the claims of the present application.
Claims
1. A passive radiation cooling coating, characterized in that, The formula includes the following parts by weight: Fluoroacrylate emulsion, 60–120 parts; Hollow glass microspheres, 40–90 parts; Nano titanium dioxide, 20–60 parts; Flake silica aerogel powder, 10–30 parts; Polytetrafluoroethylene micro powder, 3–10 parts; Hydroxyl-terminated polydimethylsiloxane, 8–20 parts; Hydroxyacrylate modified silane coupling agent, 1–5 parts; Superhydrophobic modified fluorosilicone surface additive, 0.5–3 parts; Nano-cerium oxide, 2–8 parts; 5–15 parts of aluminum fluoride-doped zinc oxide infrared enhancing powder; Deionized water, 30–60 parts; Dispersant and defoamer, 1–3 parts; Leveling agent, 0.5–1.5 parts.
2. The passive radiation cooling coating according to claim 1, characterized in that, The preparation steps of the aluminum fluoride-doped zinc oxide infrared enhancement powder are as follows: Zinc nitrate hexahydrate and aluminum nitrate were reacted according to Zn 2+ With Al 3+ The molar ratio of metal ions is 100:6–8. The metal ion concentration in the solution is adjusted to 0.1–0.2 mol / L. A 0.3–0.6 mol / L ammonia solution is added to carry out a co-precipitation reaction under pH 9–10 conditions to obtain the doped precursor powder. The obtained doped precursor powder was placed in air and heated to 450–500℃ at a rate of 5℃ / min, and held for 2–3 h to obtain primary Al-doped ZnO powder. Subsequently, low-temperature fluorination modification was performed in an ammonium fluoride atmosphere, with the temperature controlled at 300–350℃ and the time at 1.5–2 h, to form a stable F-type surface layer. - Doped layer; The fluorinated powder was dispersed in a 2 wt.% solution of γ-glycidyl ether propoxysilane in ethanol, stirred for 0.5–1 h, and then dried at 80–90 °C to obtain aluminum fluoride-doped zinc oxide infrared enhancement powder.
3. The passive radiation cooling coating according to claim 1, characterized in that, The co-precipitation reaction yields the doped precursor powder, and the specific method is as follows: The reaction temperature was controlled at 60±2℃, and the stirring speed was 400–500 rpm. After 1–2 h of reaction, a hydroxide precursor precipitate was generated. The precipitate was washed three times by vacuum filtration and then placed in a constant temperature drying oven at 100–110℃ for 7–8 h to obtain the doped precursor powder.
4. The passive radiation cooling coating according to claim 1, characterized in that, The sheet-like silica aerogel powder is prepared by freeze-directed drying to induce sheet growth, specifically including the following steps: Using tetraethoxysilane as a precursor, the mixture was prepared in a molar ratio of tetraethoxysilane:ethanol:water:hydrochloric acid of 1:4:10–15:0.05 and magnetically stirred at 20–25°C for 0.5–1 h to form a uniform silica sol. The mixture was then allowed to stand and age for 12 h to obtain a gel. The gel slices with a thickness of 3–5 mm were sequentially subjected to solvent exchange with ethanol and n-hexane, soaking for 5–6 h at each step, and repeated 2–3 times. Then, they were freeze-dried in a freeze-drying apparatus at a cooling rate of 0.2–0.4 °C / min at -50 °C for 36–48 h to induce the arrangement of the sheet structure in the direction of water sublimation, thus obtaining sheet-like aerogel blocks. The obtained block was vacuum dried at 140–150℃ for 3–4 h to remove residual solvent. The resulting aerogel was pulverized into micro flakes of 1–5 μm and placed in anhydrous toluene solution containing 2 wt.% trifluoropropyltrimethoxysilane. The mixture was refluxed for 1–2 h and then filtered and dried to obtain flake silica aerogel powder.
5. The passive radiation cooling coating according to claim 1, characterized in that, The preparation process of the hollow glass microspheres is as follows: High borosilicate hollow glass microspheres were added to a 90% (v / v) ethanol solution, and aminopropyltriethoxysilane or vinyltriethoxysilane were added as coupling agents. The concentration of the coupling agent was controlled at 2 wt.%, the pH was 4.5–5.0, the temperature was 70–80℃, and the reaction was stirred for 1–2 h. After the reaction was completed, the mixture was filtered, washed twice with ethanol, and dried at a constant temperature of 100–110℃ for 3–4 hours to obtain microbeads with a silanization layer thickness of 20–40 nm.
6. The passive radiative cooling coating according to claim 5, characterized in that, The high borosilicate hollow glass microspheres undergo pretreatment, including: The sample was selected with an average particle size of 20 μm and a true density of 0.3 g / cm³. 3 High borosilicate hollow glass microspheres with a wall thickness of 1.0–1.5 μm were first etched with a 5 wt.% dilute hydrofluoric acid solution for 25–30 s to remove the free oxide layer, and then repeatedly washed with deionized water until neutral, and dried at 100–110 °C for 1–2 h.
7. The passive radiation cooling coating according to claim 1, characterized in that, The superhydrophobic modified fluorosilicone surface additive uses fluorinated acrylic monomer, methyltriethoxysilane and hydroxyl-terminated polydimethylsiloxane as raw materials in a molar ratio of 4:1:0.5–1. The preparation method of superhydrophobic modified fluorosilicone surface additive is as follows: Fluorinated acrylic acid monomer and methyltriethoxysilane were dissolved in toluene, and azobisisobutyronitrile was added as an initiator. Free radical copolymerization was carried out at 70–75 °C for 4–5 h to obtain fluorinated acrylic acid-silane copolymer. Hydroxyl-terminated polydimethylsiloxane is condensed with a copolymer under ammonia catalysis at a temperature of 70–80°C for 2–3 hours to form an end-capped fluorosilicone copolymer additive. The solvent is removed by rotary evaporation and the product is vacuum dried at 50–60°C for 5–6 hours to obtain a transparent viscous liquid, namely a superhydrophobic modified fluorosilicone surface additive.
8. The passive radiation cooling coating according to claim 1, characterized in that, The fluoroacrylate emulsion uses methyl methacrylate, fluorooctyl acrylate and butyl acrylate as the main monomers, with a molar ratio of methyl methacrylate, fluorooctyl acrylate and butyl acrylate of 6:3:1–2. The preparation method is a semi-continuous emulsion polymerization method.
9. A passive radiative cooling coating according to claim 8, characterized in that, The fluoroacrylate emulsion is produced using a semi-continuous emulsion polymerization method, including: Add 1 wt.% sodium dodecyl sulfate as an emulsifier to deionized water, heat to 70–75°C, and stir at 200–300 rpm to form a monomer mixture; The monomer mixture was simultaneously added dropwise with 0.3 wt.% ammonium persulfate solution for 1–2 h to initiate polymerization. The reaction was maintained at 70–80 °C for 2–3 h and then cooled to 45–50 °C. 3–8 wt.% of terminal hydroxyl PDMS was introduced into the system, and 1 wt.% of 3-propyltriethoxysilane was added as a compatibilizer. The mixture was stirred at 40–50 °C for 1–2 h to allow PDMS to react and form bonds with the surface of the emulsion particles. After the reaction is complete, the pH of the system is adjusted to 7.0–7.5, and the stable emulsion, i.e., acrylate emulsion, is obtained by filtration and removal of residue.
10. A method for preparing a passive radiation cooling coating, comprising preparing the coating according to any one of claims 1-9, characterized in that, The specific steps include the following: (S1) Pre-dispersion and initial mixing of functional fillers: Hollow glass microspheres, nano titanium dioxide and flake silica aerogel powder are added to the fluoroacrylate emulsion, and polytetrafluoroethylene micro powder is added for high-speed dispersion to form a stable multi-scale scattering base slurry. (S2) Infrared enhancement and weather-resistant filler compounding integration: Add aluminum fluoride doped zinc oxide infrared enhancement powder, nano cerium oxide and hydroxyl acrylic acid modified silane coupling agent to the base slurry to form a composite system with both reflection and radiation functions. (S3) Introduction and dynamic equilibrium control of flexible segments and interface modifiers: Add hydroxyl-terminated polydimethylsiloxane, leveling agent and superhydrophobic modified fluorosilicone surface additive to adjust flexibility and surface energy and form a stable molecular-scale interface structure. (S4) System homogenization, defoaming and construction viscosity control: Vacuum defoaming, water addition and viscosity adjustment, and addition of dispersant and defoamer are performed on the system to make the solid content and fluidity of the system meet the construction requirements and obtain a uniform milky white coating. (S5) Film formation, curing and self-migration of surface structure: The film is formed by airless spraying, and then dried at low temperature and cured by self-crosslinking at room temperature to form a fluorine-rich silicon self-migration layer on the surface, achieving self-cleaning and high reflectivity. (S6) Performance testing and finished coating stabilization and packaging: The performance of the cured coating is tested, and after it is confirmed to be qualified, the finished coating is filtered and packaged for use.
Citation Information
Cited By
Spectral selective super-hydrophobic photovoltaic gain coating as well as preparation method and application thereof
CN121930729A
A spectrally selective superhydrophobic photovoltaic gain coating, and methods of making and using the same
CN121930729B
Self-layering radiation refrigeration coating material and preparation method and application thereof
CN122381633A